Optimization of electrostatic simulation by utilization of distribution equations with emphasis on design of capacitance sensors of inhomogeneity distance - Mancl, V.; Beneš, P. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper deals with the problem of optimizing the simulation of electrostatic fields with a focus on electrode setup simulations for capacitive sensor design. Several simulations were performed in Ansys electronics desktop software in Maxwell 2D and 3D module. The simulations were carried out on a sensor model with parallel plates, between which the movable inhomogeneity was placed. In the simulation, the inhomogeneity was modeled as an solid object. The proposed optimization consisted in replacing the inhomogeneity as an object by the equation of permittivity distribution in the space between the plates of the capacitor. The obtained dependences of the capacitance on the position of the inhomogeneity of the two models were compared together. Also the time required to complete the simulation was discussed. In addition to evaluating the advantages and disadvantages of the two modelling approaches, the paper describes a method for simulating a continuous gradient distribution of inhomogeneity permittivity.
Keywords: Ansys Electronics Desktop; Dielectric distribution; Maxwell 2D; Maxwell 3D; Mesh operations; Parallel plate capacitor; Simulation